DETERMINAN KINERJA DOSEN BERSERTIFIKASI DI POLITEKNIK PRATAMA MULIA SURAKARTA - Huriyah, Huriyah; Rahayu, Bakti Sri (Universitas Of Surakarta, 2022)
The success of a university is very dependent on the performance of its lecturers, for that the performance of lecturers must receive the main attention. Pratama Mulia Surakarta Polytechnic is a private university with 34 permanent lecturers, 28 of whom have been certified, of which 64% are over 50 years old. With an age that is no longer young, the lecturers are required to continue to have good performance by always following changes in both teaching, research and community service.This study aims to examine the effect of competence, work motivation, commitment, lecturer certification and work discipline on the performance of certified lecturers at Politama Surakarta. The population in this study were all 27 certified lecturers. Data was obtained by distributing questionnaires to all lecturers who were certified lecturers. The empirical test uses Multiple Regression with the dependent variable: Lecturer Performance and 5 independent variables: competence, work motivation, commitment, lecturer certification and work discipline. The results showed: competence and commitment affect the performance of lecturers; while work motivation, lecturer certification and discipline do not affect lecturer performance. With this research, it is hoped that it can be used as input to improve the performance of certified lecturers.